Student’s Mastery Of Grammar In Simple Present Tense - M. Dzaki Sholihin; Liana Pertiwi; Yani Lubis (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
This journal aims to analyze students' level of grammar mastery in using Simple Present Tense at school. Research was carried out through data collection. The results of the analysis show that the majority of students still experience difficulties in mastering the use of Simple Present Tense. There are common mistakes such as using inappropriate auxiliary words, adding -s/es to the wrong verb, and using inappropriate adverbs of time. However, there are some students who show good mastery in using this tense. In conclusion, this research shows the importance of supporting students' grammar mastery in the Simple Present Tense. Educators need to provide appropriate exercises, such as using example sentences and direct interaction in class, to help students overcome their difficulties and improve their mastery of these tenses. Apart from analyzing the difficulties students face in mastering the Simple Present Tense, this research also explores factors that might influence their mastery. Factors such as language background, training intensity, and grammar teaching methods were also considered in this study. The research results show that students' language background can influence the level of mastery of Simple Present Tense grammar. Students who have a language background that is more similar to English tend to have better abilities in understanding and applying these tenses.